Financialization and the labor share of income - Onur Özdemir (Review of Economic Perspectives, 2019)
Financialization has been growing importance in macroeconomic perspectives since the finance-dominated capitalist relations have captured many of the specific positions in an aggregate economy. However, the empirical literature has substantially ignored the examination of the link between an increasing scale of financialization and the rising income inequality. In this study, a major hypothesis is based on the fact that the finance-dominated capitalism has a considerable effect on distributional practices through the channels of bargaining power. By applying the Kaleckian approach, the paper investigates the relationship between financialization and the labor share of national income using a panel dataset of 52 countries over the 1992-2012 period. The results suggest that a higher level of stock market development leads to a more unequal distribution of income and, thus, to the decline of wage share in the national income. Other factors such as globalization and technical change can also exacerbate the decline of wages, coupled with a decrease in the bargaining position of labor measured by unemployment rate and labor force participation rate.
Keywords: E01; E25; J53; 330; Bargaining Power; Financialization; Globalization; Labor Share; Stock Markets